2009
DOI: 10.1007/s11270-009-0190-x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Goosegrass (Eleusine indica) to Remediate Soil Contaminated with Petroleum

Abstract: A greenhouse experiment was performed to evaluate effectiveness of goosegrass (Eleusine indica) in phytoremediation of soil contaminated with 8,247 mg kg −1 of total petroleum hydrocarbons (TPH). We determined seed germination toxicity, soil microbial viable counts, catalase activity, dehydrogenase activity (DHA), and the concentrations of TPH and 14 polycyclic aromatic hydrocarbons (PAHs) in soil and plant tissue. After 5 months, the initial level of contamination was reduced by 47% in planted soil, whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…After 9 months of plant growth, 43 and 70% decline in APH concentration were observed in soil AC and FC, respectively. Lu et al reported that the concentration of petroleum contamination in the rhizosphere of Eleusine indica was reduced by 47% after 5 months of plant growth while only 11% of reduction was observed for the unplanted soil. Nisa and Rashid observed that the concentration of phenanthrene, pyrene, and benzo[a]pyrene significantly decreased in the soil under 120 days of V .…”
Section: Discussionmentioning
confidence: 99%
“…After 9 months of plant growth, 43 and 70% decline in APH concentration were observed in soil AC and FC, respectively. Lu et al reported that the concentration of petroleum contamination in the rhizosphere of Eleusine indica was reduced by 47% after 5 months of plant growth while only 11% of reduction was observed for the unplanted soil. Nisa and Rashid observed that the concentration of phenanthrene, pyrene, and benzo[a]pyrene significantly decreased in the soil under 120 days of V .…”
Section: Discussionmentioning
confidence: 99%
“…The root system of higher plants is associated not only with soil environment but also with a vast community of metabolically active microorganisms. The living plants create unique habitats on and around the roots where the microbial population is considerably higher than that of root free soil environment (Lu et al 2010). Around 40 % of a plant's photosynthate can be exuded by plant roots into the soil as sugars, organic acids, and aromatic compounds, which are rich in carbon and energy for microorganisms' growth (Khan et al 2013).…”
Section: Bioremediation Technique Using Plantsmentioning
confidence: 99%
“…The lack of environmental specifications for the restoration of contaminated soils constitutes one of the principal factors of uncertainty with respect to the effectiveness of remediation actions. Although many techniques are effective in reducing the overall hydrocarbon concentration in the soil (Volke and Velasco 2002), these methods do not necessarily restore the physical and chemical properties of the soil that may be affected by petroleum spills, impeding future site use (Adams et al 2008b;Lu et al 2010).…”
Section: Introductionmentioning
confidence: 99%